HEART DISEASE IN CHILDREN WITH RESPIRATORY INFECTIONS - I. V. Babachenko; A. S. Levina; S. N. Chuprova; E. V. Sharipova (Журнал инфектологии)
The link between heart disease and infectious pathogens is well known. Despite the high frequency of cardiac pathology in infectious diseases, it is rarely diagnosed because of lack of specific clinical  and  laboratory  symptoms. It is especially  difficult to diagnose in  children. Airborne  infections in the structure of infectious morbidity of children occupy a leading place.The aim of this work was to study the nature of the lesions of the heart  in children suffering from acute infection of the respiratory tract.Materials and  methods: 341 children with acute respiratory infection of moderate severity were surveyed by a method of ECG dispersion mapping. Cardiac  pathology has not previously been determined in these children. Signs of disease of the heart was identified in 76 children (22%). Further study included instrumental (ECG, ECHO-KG,  daily monitoring of ECG), biochemical and  etiological (ELISA, PCR, immunocytochemical) research  methods for determining the nature of the damage to the heart and the etiology of the disease.Results. Myocarditis was diagnosed in 2%  of children, a violation of repolarization – in 21%,  heart  rhythm disorders  – in 35%  (AV – blockade in 4%).  Most  often  signs  of heart disease were detected in children with Epstein-Barr virus (32%), streptococcal (28%), cytomegalovirus (25%), herpesvirus type  6 infection (24%). Pathogens from the  group of acute respiratory virus infections were identified in 28%, enterovirus – in  10%,  Haemophilus influenzae – in  10%, Mycoplasma pneumonia – in 10%,  Pneumococcus – in 9%, Chlamydia – in 9%, Parvovirus B19 – in 6%.Conclusion. Sensitive screening test  to  detect cardiac pathology is the method of ECG dispersion mapping. Heart damage in children with respiratory diseases in 60% of cases is associated with  mixed infections. Timely  diagnosis of lesions of the heart in infectious diseases in children allows to adjust the therapy in the early stages  and prevent the development of chronic  pathology of the heart.